The students’ attitude on teachers’ code-switching in teaching english at islamic middle school - Maratus Shalihah; Hamzah Hamzah (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2022)
This study determined the The Students’ Attitude on Teachers’ Code-switching in Teaching English at VIII grade MTSN Agam. Attitude is committed by someone’s beliefs about attributes or outcomes of performing such as affective behavior and cognitive weighted by evaluations of those outcomes or attributes. Attitude in teaching English as foreign language in Indonesia is one of the crucial factors determining the success or failure of learning. The perrspective of attitude was measured how the teacher teach at the classroom,  then how was the result process of learning to theteacher. This s research was drawn from the result of  observation and questionnaire. The subject was the students at MTsN Agam (MTsN 6 and MTsN 7). This was a quantitative approach.The result revealed that students have possitive attitude toward code-switching. The findings indicate that the concept of attitude has three components, such as affective, behavioral, and cognitive.